8.5 THE NUMBER OF THE NEED FOR TECHNIQUES DEVELOPMENT OF THE METHOD OF DETERMINATION - Maksudov Zokir Talibjanovich, Kudaybergenov Mavlyan Saidakbarovich, Abdukarimova Shoxsanam Murodjon qizi assistent (Innovative technologies in construction Scientific Journal, 2024)
This article discusses the results of a study to develop a methodology for calculating the need for road equipment and special machines for the construction and repair of highways. As a result, a flowchart algorithm has been developed to calculate the need for road equipment and special machines for the construction and repair of highways. Key words: automobile road, construction, productivity, road machines, mechanism, norma, power, metod, algoritm. Introduction. Determining the number of vehicles required for road construction and repair works can be done in several ways, including: using the equipment’s time availability, work efficiency and regulatory documents. In most cases, which method to use, it is necessary to pay attention to the main indicators of road equipment, indicators of road work, the types of road construction and special machines that affect the work process, their main parameters, their compatibility with each other in terms of work performance, and other parameters. Method. Determining the number of necessary equipment required for construction and repair work on highways, road construction and special machines and mechanisms based on the daily operating efficiency and time standards available normative documents SNiP, ENiR, MShN. It is determined by the following expression using the values of MQN, SNiP, and ENiR = in expression – duration of daily working hours, = 8,0; – normative time in normative documents SNiP, ENiR, MShN. For the unit of measurement given in MQN, SNiP and ENiR, i.e. to perform work volume [V]; – standard volume of work, MShN in regulatory documents. For the unit of measurement specified in MQN, SNiP and ENiR.